Psychological Battle of Death in Sri Aurobindo‟s Savitri - Chandrayan, Bharati (International Journal of Psychosocial Rehabilitation, 2020)
Her soul arose, confronting Time and Fate. Immobile in herself, she gathered force. This was the day when Satyavan must die. (END OF CANTO ONE). Sri Aurobindo’s epic Savitri narrates the victorious struggle of the mythical character Savitri against the invincible Death. It is a glorious account of the rejuvenation of dead Satyavan by the undaunted spiritual battle of Savitri involving immeasurable psychological turmoil. This paper explores how mankind goes through the psychological agony of death. The mind is adversely affected, and unseen depression engulfs life. Savitri, the representative of the human spirit, had incessantly fought against death, and that was not a small feud but a long, unyielding battle against the god of death. Goddess Savitri ignites the consciousness of mankind and redeems it from the tangles of death. Death after life is the sign of the dawn of evolution. The phase of evolution is the elevation towards expansion of mind and soul.